(3Lfi GdLfGSs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eSde GdCRgQi s)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPi CUWai gPG CdaJg ai CbSGe GdLfGS GdJi GSJNQLJgG hMUQJgG hSejJg Lfi GdLfGS hHGddg CYhP QH GdfGS Cbhd CUhd CfhGY GdLfGS NeSI YTQ fhYkG s
(3BNQgG (B:s
(3hce Hg UM eYJd hdGM dg fhQ hfGQ ef GdJhajb hGdgee HOQ GdJeGe GdPi CMjG HWdYJg djd GdJeGe eVGa Gdjhe HGdNOe Je Pdc BNQg hGdMeO ddg hMOg hMSHfG Gddg hfYe Gdhcjd s
(3fSNI CNQis
(3cJHg GdfGSN dSjOg eMeO Hf GdTjN Ydi GdeMdis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GddZIs